Correlates of heroin and methamphetamine use among homeless male ex-jail and prison offenders. (December 2014) - Nyamathi, Adeline M.; E. Salem, Benissa; Farabee, David; Hall, Elizabeth; Zhang, Sheldon; Marfisee, Mary; Khalilifard, Farinaz; Musto, Stephanie; Faucette, Mark; Leake, Barbara
<x xml:space="preserve">Abstract</x> Homeless men exiting California State jails and prisons are a heterogeneous community with varied childhood, incarceration and drug use histories. This cross-sectional study assessed whether homeless men who were discharged from either jail or prison into a residential substance abuse treatment program, differed in terms of methamphetamine and heroin use. This study utilized baseline data collected on 540 recently paroled men randomized to one of three programs that assessed the impact of a peer coaching intervention on subsequent drug use and reincarceration. We found that younger ex-offenders exiting prisons and jails were more likely to have used methamphetamine alone, whereas African–American ex-offenders were less likely to have used methamphetamine alone when compared to other ethnic groups. Further, ex-offenders exiting jails and self-reporting use of heroin only at baseline were significantly more likely than their counterparts to have been removed from home before age 18 years. For men exiting jails, there was an association between lower self-esteem and having used methamphetamine but not heroin. However, having used both heroin and methamphetamine was associated with both violent crime and cognitive problems in both jail and prison samples. Our findings showcase the need to understand unique correlates of both heroin and methamphetamine as they relate to jail and prison populations.